Commutative Matrix-based Diffie-Hellman-Like Key-Exchange Protocol - Chefranov, Alexander G.; Mahmoud, Ahmed Y. (Springer, 2013)
A matrix-based Diffie-Hellman-like key exchange protocol and utilizing it secure key-exchange protocol similar to HMQV are proposed. The proposed key exchange protocol uses matrix multiplication operation only; it does not rely on the complexity of the discrete logarithm problem contrary to the prototype and its known variants. Two-way arrival at the common key, similar to that employed in the Diffie-Hellman protocol, is provided by specially constructed commutative matrices. The trap-door property ensuring the proposed protocol security is based on exploiting of a non-invertible public matrix in the key generating process.
28th International Symposium on Computer and Information Sciences (ISCIS) -- OCT 28-29, 2013 -- Inst Henri Poincare, Paris, FRANCE